Difference Analysis of the Implementation of Ten Steps to Successful Breastfeeding between Private and Public Hospitals in District of Kudus - Kudarti Kudarti; Martha Irene Kartasurya; Siti Fatimah Pradigdo (Jurnal Manajemen Kesehatan Indonesia, 2015)
ABSTRAKSepuluh Langkah Menuju Keberhasilan Menyusui (LMKM) merupakan kunci keberhasilan pemberian ASI Eksklusif. Pelaksanaan 10 LMKM di rumah sakit Kabupaten Kudus dipengaruhi oleh sistem birokrasi yang berbeda antara rumah sakit swasta dan pemerintah. Penelitian ini bertujuan menganalisis perbedaan implementasi sepuluh langkah menuju keberhasilan menyusui antara rumah sakit swasta dan pemerintah di Kabupaten Kudus. Desain penelitian adalah kualitatif. Subjek penelitian untuk setiap rumah sakit adalah kepala ruang bersalin, bidan KIA, 2 dokter spesialis kebidanan, 3 bidan ruang nifas sebagai informan utama. Informan triangulasi meliputi direktur,manajer keperawatan, 3 pasien nifas dan 2 pasien hamil dari setiap rumah sakit. Data dikumpulkan melalui wawancara mendalam dan dianalisis dengan analisis isi. Hasil penelitian menunjukkan perbedaan implementasi 10 LMKM di rumah sakit swasta dan pemerintah. Hal yang belum dilaksanakan di rumah sakit swasta adalah tersedianya susu formula tanpa indikasi, rawat gabung masih parsial (2 jam setiap hari), kurangnya dukungan terhadap ibu dalam pemberian ASI sesuai kemauan bayi, tersedianya dot dan belum terbentuk KP-ASI. Hal tersebut berkaitan dengan keterbatasan sumber daya, komitmen implementor yang masih rendah dan lingkungan eksternal yang belum mendukung. Rumah sakit pemerintah belum melaksanakan penyuluhan kepada ibu hamil dan pembentukan KP-ASI. Hal tersebut disebabkan keterbatasan sumber daya khususnya pendanaan untuk pelatihan dan pengadaan media penyuluhan. Rumah sakit swasta diharapkan untuk meningkatkan pelayanan kebidanan sesuai standar sistem akreditasi rumah sakit dari pemerintah. Rumah sakit pemerintah disarankan meningkatkan anggaran untuk pelatihan dan pengadaan media penyuluhanKata kunci : Implementasi, Sepuluh Langkah Menuju Keberhasilan Menyusui, Rumah Sakit, Swasta, PemerintahABSTRACTTen Steps to Successful Breastfeeding (TSSB) is a key of successful exclusive breastfeeding. The implementation of TSSB at hospitals in District of Kudus was influenced by a difference bureaucratic system between private and public hospitals. This research aimed to analyze the difference of the TSSB implementation for successful breastfeeding between private and public hospitals in District of Kudus. This was qualitative research. Main informants encompassed head of childbirth room, midwives of Maternal and Child Health, 2 obstetricians, and 3 midwives at post-natal room. Meanwhile,informants for triangulation purpose encompassed director, manager of nursing, 3 post-natal patients, and 2 pregnant women at each hospital. Data were collected by in-depth interview and analysed using a method of content analysis. The result of this research showed that some differences of the implementation of TSSB between private and public hospitals were as follows: at private hospitals, there was any formula milk without indication, joined treatment room was still partial (2 hours a day), and there was lack of support for mother in providing breastfeeding in accordance with babies’ need. In addition, there was any dot and there was no a support group of breastfeeding. These problems were due to limitation of resource, low commitment of an implementer, and lack of external environment support. In contrast, public hospitals had not provided information to pregnant women and had not formed a support group of breastfeeding. These problems were due to limitation of resource particularly funding for training and providing information media. As suggestions, private hospitals need to improve midwifery services in accordance with a standard of a hospital accreditation system from the government. In addition, public hospital need to increase funds for training and providing information media.Keywords : Implementation, Ten Steps to Successful Breastfeeding, Hospital, Private, Government